Adult T-cell leukemia/lymphoma: A pending challenge - Álvarez, Carolina (2024)
Adult T-cell leukemia/lymphoma (ATLL) is a post timic T-cell neoplasia of poor prognosis and difficult management. It has been etiologically associated with Human T-lymphotropic virus 1 (HTLV-1), a retrovirus that has been identified in endemic regions such as Japan, Western Africa, the Caribbean islands and South America. In Perú, it is estimated that 1-2% of the population carries the virus. The lifetime risk for an HTLV-1 carrier to develop ATLL is 5%. Given the endemicity of this infection in our setting and the poor overall prognosis of ATLL, there is a need for novel therapeutic strategies and preventive interventions. In this review, we explore the clinical and epidemiological characteristics of ATLL and its therapeutic options.